Exploring mechanism of hidden, steep obliquely inclined bedding landslides using a 3DEC model: A case study of the Shanyang landslide in Shaanxi Province, China - Jia-yun Wang; Zi-long Wu; Xiao-ya Shi; Long-wei Yang; Rui-ping Liu; Na Lu (China Geology)
ABSTRACT: Catastrophic geological disasters frequently occur on slopes with obliquely inclined bedding structures (also referred to as obliquely inclined bedding slopes), where the apparent dip sliding is not readily visible. This phenomenon has become a focal point in landslide research. Yet, there is a lack of studies on the failure modes and mechanisms of hidden, steep obliquely inclined bedding slopes. This study investigated the Shanyang landslide in Shaanxi Province, China. Using field investigations, laboratory tests of geotechnical parameters, and the 3DEC software, this study developed a numerical model of the landslide to analyze the failure process of such slopes. The findings indicate that the Shanyang landslide primarily crept along a weak interlayer under the action of gravity. The landslide, initially following a dip angle with the support of a stable inclined rock mass, shifted direction under the influence of argillization in the weak interlayer, moving towards the apparent dip angle. The slide resistance effect of the karstic dissolution zone was increasingly significant during this process, with lateral friction being the primary resistance force. A reduction in the lateral friction due to karstic dissolution made the apparent dip sliding characteristics of the Shanyang landslide more pronounced. Notably, deformations such as bending and uplift at the slope's foot suggest that the main slide resistance shifts from lateral friction within the karstic dissolution zone to the slope foot's resistance force, leading to the eventual buckling failure of the landslide. This study unveils a novel failure mode of apparent dip creep-buckling in the Shanyang landslide, highlighting the critical role of lateral friction from the karstic dissolution zone in its failure mechanism. These insights offer a valuable reference for mitigating risks and preventing disasters related to obliquely inclined bedding landslides.